Three days in the hermit kingdom : an American visits North Korea - Burdick, Eddie, 1962- (McFarland & Co., 2010)
"This book chronicles a rare, regime-sanctioned excursion by a North American into the heart of the Democratic People's Republic of Korea. As a Korean speaker, the author gathered more information than the scripted, regime-approved English narration provided by his Korean guides. Behind the propaganda of the Communist regime, the unscripted, authentic, eye-opening North Korea is revealed"--Provided by publisher.